THE EFFECT OF CAPITAL STRUCTURE, COMPANY SIZE, PROFITABILITY AND DIVIDEND POLICY ON THE VALUE OF FOOD AND BEVERAGE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2017-2021 PERIOD - Wilda Nafisa; Chairil Akhyar; Marzuki; Faisal Matriadi (PT. Radja Intercontinental Publishing, 2023)
This study examines the effect of capital structure, firm size, profitability, and dividend policy on the value of food and beverage companies listed on the Indonesia Stock Exchange during 2017-2021. This study uses secondary data, and the samples are 10 food and beverage companies listed on the Indonesia Stock Exchange during 2017-2021. The sampling technique used purposive sampling technique. The data analysis method used is the panel data regression analysis method. The results indicate that capital structure positively and significantly affects firm value, firm size positively and significantly affects firm value, profitability has no significant effect on firm value, and dividend policy positively and significantly affects the value of food and beverage companies listed on the Indonesia Stock Exchange for 2017-2021.